HUBUNGAN ANTARA UMUR DAN STATUS GIZI IBU BERDASARKAN UKURAN LINGKAR LENGAN ATAS DENGAN JENIS BBLR DI PUSKESMAS TAWANGREJO KOTA MADIUN - Eny Pemilu Kusparlina (AKADEMI KEBIDANAN HARAPAN MULYA PONOROGO, 2019)
Low Birth Weight incidence is caused by several factors including maternal age <20/> 35 years and LILA <23.5 cm. The results of the preliminary study at the TawangrejoCommunity Health Center in the City of Madiun, from 2016 there were 20 Low Birth Weightwhile in January-June 2017 there were 24 Low Birth Weight. The problem of this study isthe increase in the incidence of Low Birth Weight.To analyze the relationship between age and maternal nutritional status based on thesize of the upper arm circumference with the type of Low Birth Weight.This study is an analytical cross-sectional study with a population of all infants withbirth weight less than 2500 gram in January-April 2011 taken by simple random sampling of23 infants. Data sourced from secondary data in the form of medical records. Theindependent variables of maternal age and nutritional status based on the size of the upperarm circumference and the dependent variable type Low Birth Weight were then analyzedusing the Fisher Exact test.This study showed that the majority (69.6%) of mothers giving birth in the agecategory were not safe, causing premature Low Birth Weight (38.5%) and Low Birth Weightat term (61.5%). And most (65.1%) mothers gave birth in the category of Lack of ChronicEnergy, causing premature Low Birth Weight (38.5%) and Low Birth Weight dismatured(61.5%). From the Fisher Exact test results obtained value p = 0.011 for age and p = 0.024for LILA size with a significance level of α = 0.05, because p <α then H1 is accepted.This study has a relationship between age and maternal nutritional status based on thesize of the upper arm circumference with the type of Low Birth Weight. Pregnant and givingbirth at an unsafe age and Lack of Chronic Energy tend to give birth to babies with LowBirth Weight. From the research conducted, it is expected that health workers will furtherimprove health promotion by carrying out prevention through early detection of pregnancyby early ANC examination with the 7T standard.